(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
online banking and mobile commerce. So in our developing economy, people also need a less complex and secure mode of payments and mobile banking. According to reports published by Business Standard [1], cashless payments in October 2016 increased 22%, when Till a few years ago, nobody imagined that mobile phones would be used to transfer money and complete shopping transactions. But now, one doesn’t really have to visit a bank, stop by at an ATM, or carry a plastic credit or debit card to make purchases. Mobile banking through mobile apps now days are on boom. The continuous increase in mobile banking users is due to technological advancements which has restored and increase the faith of users towards mobile banking and different payment modes. In a developing country like India, where mobile users are growing at very fast speed, because of the low cost smart phones and people can also afford that technology, the problems and complexity will also growing rapidly. Users expectations in terms of speed, convenience and security are now a days a major concern. The technologies like NEFT, IMPS, RTGS etc. have been functioning very well but what next? What is the future of mobile banking? To make sure that mobile payments stay in the market in future and it is used by most users, the national payment corporation of India has initiated a new payment system called as unified payment interface(UPI) that make online payments much easier without requiring a digital wallet or credit or debit card. You either need to know the other’s person MMID (mobile money identifier) or a Virtual Payment Address (VPA) and phone number. All these features of UPI will surely boost the confidence of e-commerce and m-commerce customers as they won’t have to go through the hassled process entering the credit/debit card information every time and also no need of remembering the bank account numbers, IFSC code and several pins associated with several bank accounts.